Auditor Reputation Concerns, Legal Liability, and Standards - Rothenberg, Naomi R. (The Accounting Review, 2020)
ABSTRACT This paper studies how legal liability due to negligence can weaken or strengthen an auditor's reputation concerns in the client market to provide high audit effort. A negligence liability rule relies on auditing standards to provide a threshold for the level of due care. When the negligence standard is lax, legal liability can weaken the auditor's reputation incentives, with lower audit effort than without legal liability. If the damage payment is low, noncompliance is less costly, because with compliance, reputational concerns cause the auditor to provide higher costly audit effort than the standard. In this case, investors also prefer noncompliance, and earnings quality is lower than if there were no legal liability damages. When the standard is stringent, noncompliance is less costly for the auditor, and legal liability strengthens reputation incentives. Investors may also prefer noncompliance, and earnings quality is higher than if there were no legal liability damages. JEL Classifications: M41; M42; D82; M48.